A. Illustrates the GO enrichment analysis pathway diagram for gene IRF4, where the x-axis denotes the count of enriched genes, and the y-axis represents the enrichment significance. - Min-xiao Wang (20868922) (2025)
B. Depicts the KEGG enrichment analysis pathway diagram for gene IRF4, with the x-axis indicating the number of enriched genes and the y-axis signifying the enrichment significance. C. Displays an alternative aspect of the GO enrichment analysis pathway diagram for gene ELANE, wherein the x-axis specifies the gene ratio, and the y-axis depicts the enrichment significance. D. Showcases the KEGG enrichment analysis pathway diagram for gene ELANE, with the x-axis indicating the gene ratio and the y-axis denoting the enrichment significance.